How important is the role of iterative liver direct surgery in patients with hepatocellular carcinoma for a transplant center located in an area with a low rate of deceased donation? - Pagano, Duilio; Khouzam, Simone; Magro, Bianca; Barbara, Marco; Cintorino, Davide; di Francesco, Fabrizio; Li Petri, Sergio; Bonsignore, Pasquale; Calamia, Sergio; Deiro, Giacomo; Cammà, Calogero; Canzonieri, Marco; et al. (Frontiers in Oncology, 2022)
Introduction Hepatocellular carcinoma (HCC) accounts for nearly 90% of primary liver cancers, with estimates of over 1 million people affected by 2025. We aimed to explore the impacting role of an iterative surgical treatment approach in a cohort of HCC patients within the Milan criteria, associated with clinical risk factors for tumor recurrence (RHCC) after liver transplant (LT) and loco-regional therapies (LRT), as well as liver resection (LR) and/or microwave thermal ablation (MWTA). Methods We retrospectively analyzed our experience performed during an 8-year period between January 2013 and December 2021 in patients treated for HCC, focusing on describing the impact on preoperative end-stage liver disease severity, oncologic staging, tumor characteristics, and surgical treatments. The Cox model was used to evaluate variables that could predict relapse risks. Relapse risk curves were calculated according to the Kaplan–Meier method, and the log-rank test was used to compare them. Results There were 557 HCC patients treated with a first-line approach of LR and/or LRTs (n = 335) or LT (n = 222). The median age at initial transplantation was 59 versus 68 for those whose first surgical approach was LR and/or LRT. In univariate analysis with the Cox model, nodule size was the single predictor of recurrence of HCC in the posttreatment setting (HR: 1.61, 95% CI: 1.05–2.47, p = 0.030). For the LRT group, we have enlightened the following clinical characteristics as significantly associated with RHCC: hepatitis B virus infection (which has a protective role with HR: 0.34, 95% CI: 0.13–0.94, p = 0.038), number of HCC nodules (HR: 1.54, 95% CI: 1.22–1.94, p < 0.001), size of the largest nodule (HR: 1.06, 95% CI: 1.01–1.12, p = 0.023), serum bilirubin (HR: 1.57, 95% CI: 1.03–2.40, p = 0.038), and international normalized ratio (HR: 16.40, 95% CI: 2.30–118.0, p = 0.006). Among the overall 111 patients with RHCC in the LRT group, 33 were iteratively treated with further curative treatment (12 were treated with LR, two with MWTA, three with a combined LR-MWTA treatment, and 16 underwent LT). Only one of 18 recurrent patients previously treated with LT underwent LR. For these RHCC patients, multivariable analysis showed the protective roles of LT for primary RHCC after IDLS (HR: 0.06, 95% CI: 0.01–0.36, p = 0.002), of the time relapsed between the first and second IDLS treatments (HR: 0.97, 95% CI: 0.94–0.99, p = 0.044), and the impact of previous minimally invasive treatment (HR: 0.28, 95% CI: 0.08–1.00, p = 0.051). Conclusion The coexistence of RHCC with underlying cirrhosis increases the complexity of assessing the net health benefit of ILDS before LT. Minimally invasive surgical therapies and time to HCC relapse should be considered an outcome in randomized clinical trials because they have a relevant impact on tumor-free survival.